"Mass" Housing in the Social and the Post-Social Worlds: Reading Hannah Arendt's "Mass Society". Issue 3 (1st October 2020) - Stoane, Andrew
Abstract: In The Human Condition (1958), Hannah Arendt predicated her thesis on societal introspection on what she called "mass society" – a population which had rapidly grown, urbanized and atomized, bringing new imperatives for humans to live together in vast numbers and with closer proximities. Throughout, Arendt discusses how shifting boundaries of public and private define our cities and our lives. As her mass society of three billion now approaches eight billion, how has the relationship between public and private – city and household – played out in the staggering population growth of the sixty years since her book? This article will explore how these six decades since the publication of The Human Condition have seen fundamental transformations in the way we understand what we now call housing, its relationship with the city, and its relationship with collective life.